Terapi Aktivitas Kelompok Lansia dengan Senam Lansia dan Pengukuran Tekanan Darah di Panti Lanjut Usia Lydia di Kota Tomohon - Stella Rasu; Eireine Maria Pandoh; Kansia A. Terok; Sr.Monika Suparlan (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2024)
The Lydia Elderly Home in Tomohon City, operating under the Kasih Agape Family Foundation, serves as a sanctuary for seniors facing a myriad of health challenges, including hypertension and Alzheimer's dementia. The serene and temperate environmental conditions present a conducive backdrop for health interventions. This study aims to assess the effectiveness of group activity therapy through elderly exercise in managing blood pressure and enhancing the quality of life for seniors afflicted with Alzheimer's dementia.A situational analysis and policy identification were conducted to design an appropriate intervention program. Preliminary findings indicate that an elderly individual with a history of hypertension exhibited a reduction in blood pressure following participation in elderly exercise. Additionally, there were signs of improved psychosocial well-being and a decrease in dementia symptoms among other participants.Conclusion: Elderly exercise as a group activity therapy demonstrates significant potential in managing blood pressure and improving the psychosocial well-being of the elderly at the Lydia Elderly Home. This program offers a holistic approach that supports the physical and mental health of the elderly, which is crucial for integration into the home's daily regimen.